Star Analysts' Voting in Emerging Market: A Perspective of Analysts' Optimistic Bias. Issue 5 (9th April 2023) - Guo, Yongzhen; Yang, Shengzhi; Wang, Yinghuan; Yi, Zhihong
ABSTRACT: We examine the effect of fund managers' voting on the optimistic bias of sell-side analysts by exploiting the exogenous event of New Fortune Magazine suspending the Sixteenth Star Analyst Contest . Our results show that the disappearance of voting makes analysts face less pressure from funds, which leads to less optimistic bias and lower error in earnings forecasts. Moreover, the effect is more pronounced in the samples of analysts who work in small brokerages and have less star experience. Further, we find that analysts reduce listed firm joint site visits with small fund managers but still conduct single site visits, suggesting analysts are diligent but not catering to small fund managers anymore. In addition, we find the opposite result as the effect of the cancelation reverses. In general, our findings indicate that the voting right of the star analyst ranking has become a self-interest tool for fund managers, driving analysts to provide biased reports and soft services, becoming another source of pressure for analysts.